2008
DOI: 10.1152/ajpgi.00272.2007
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase plays a crucial role in the activation of pancreatic stellate cells

Abstract: Activated pancreatic stellate cells (PSCs) play an important role in pancreatic fibrosis and inflammation, where oxidative stress is implicated in the pathogenesis. NADPH oxidase might be a source of reactive oxygen species (ROS) in the injured pancreas. This study aimed to clarify the expression and regulation of cell functions by NADPH oxidase in PSCs. PSCs were isolated from rat and human pancreas tissues. Expression of NADPH oxidase was assessed by reverse transcription-PCR and immunostaining. Intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 43 publications
4
92
0
Order By: Relevance
“…[13][14][15][16][17][18] The precise mechanisms underlying islet fibrosis are largely unknown, although the deposition of islet amyloid, activation of RAS and oxidative stress have all been implicated. 16,17,[28][29][30] Our demonstration of a specialized ISC population in rodent islets is consistent with an important role for these cells in islet fibrosis, in an analogous manner to that of classical PSCs in pancreatic fibrosis. 11,25,26 This proposal is supported by several recent studies suggesting that ISCs might play an important role in islet fibrosis in T2DM.…”
Section: -1227supporting
confidence: 72%
See 2 more Smart Citations
“…[13][14][15][16][17][18] The precise mechanisms underlying islet fibrosis are largely unknown, although the deposition of islet amyloid, activation of RAS and oxidative stress have all been implicated. 16,17,[28][29][30] Our demonstration of a specialized ISC population in rodent islets is consistent with an important role for these cells in islet fibrosis, in an analogous manner to that of classical PSCs in pancreatic fibrosis. 11,25,26 This proposal is supported by several recent studies suggesting that ISCs might play an important role in islet fibrosis in T2DM.…”
Section: -1227supporting
confidence: 72%
“…22 The diabetic environment provides numerous signals which could lead to stellate cell activation. Thus, previous studies using classical PSCs have demonstrated that hyperglycemia, 16,31 activation of the RAS, 32 oxidative stress, 17,30 platelet-derived growth factors, 33 and inflammatory cytokines 34 all enhance PSC activation and proliferation. The environment of the diabetic islet is characterized by the presence of the hyperglycemia [35][36][37] and oxidative stress, [38][39][40] as well as macrophage infiltration and increased expression of inflammatory molecules such as IL-1, IL-6, TNF-α, MCP-1, and MIP-1α.…”
Section: -1227mentioning
confidence: 96%
See 1 more Smart Citation
“…Other NOX isoforms that are reported to contribute to tissue fibrosis in nonpulmonary organ systems include NOX1 (4,75,112,139) and NOX2 (67,75,89,112,143). A p47 phox -requiring NOX isoform is required for the development of fibrosis in a murine lung-injury model that is inflammation dependent, and the observed protection in p47 phoxÀ=À mice is associated with enhanced neutrophilic inflammation and matrix metalloproteinase (MMP)-9 activity (70).…”
Section: Nox Enzymes In Pulmonary Fibrosismentioning
confidence: 99%
“…Although therapeutic strategies focusing on the elimination of superoxide have been developed in animal models and in clinical cases, the effects of such reagents are still unclear [11,[30][31][32]. Therefore, in this study, we investigated whether inhalation of apocynin may influence hydrogen peroxide, nitrite and nitrate concentrations in airways in healthy subjects.…”
mentioning
confidence: 99%